Delimiting the eastern extent of the Altyn Tagh Fault: Insights from structural analyses of seismic reflection profiles. (30th June 2020) - Zhang, Yuqing; Zhang, Fengqi; Cheng, Xiaogan; Lin, Xiubin; Chen, Hanlin; Wyrwoll, Karl‐Heinz; Wu, Lei; Chen, Jie; Krapež, Bryan; Lu, Yanchou; Ding, Weiwei; An, Kaixuan; et al.
Abstract: The Altyn Tagh Fault (ATF) serves as a key continental‐scale controlling structural element of the Tibetan Plateau. However, its eastward extent remains controversial. Here we use high‐resolution seismic reflection profiles to investigate the subsurface structures of the easternmost ATF and use these to delimit the easternmost extent of the fault. The structural analyses show an eastward geometric change from transpressional positive flower structures to compressional thrusts, with transpression‐induced shortening magnitudes decreasing eastwards from a maximum of ~5.3 km to being absent. Stratigraphic controls indicate that the deformation took place over the last ~<1.2 Ma. Our wider findings lead us to: (a) reject the suggestion that the ATF previously extended beyond the Kuantan Shan‐Hei Shan to link with the Alxa‐East Mongolia Fault; and (b) propose that the rigid block model used to describe the Tibetan Plateau crust is not consistent with the extent and structural details of the easternmost ATF.